INNER STRUCTURE AND LOCAL WISDOM IN NYANGAHATN BABURUKNG ORAL TRADITION OF DAYAK KANAYATN - Sesilia Seli (Balai Bahasa Provinsi Daerah Istimewa Yogyakarta, 2021)
Nyangahatn Baburukng is the mantra of the Kanayatn Dayak community that is uttered at the Baburukng ritual as the initial stage of the farming tradition (bahuma). This study was conducted to provide a deeper meaning to the inner structure and local wisdom of the Nyangahatn Baburukng and as a means of inheritance to the next generation. The objective of this study is to analyze the inner structure and forms of local wisdom in Nyangahatn Baburukng. The study is based on theories of local wisdom, mantra, and structure of mantra by using qualitative descriptive methods, objective approaches and sociology of literature. The results of this study indicate that the inner structure of the Nyangahatn Baburukng text includes (1) The theme includes belief in Jubata as a helper and giver of blessings; carefully reading the signs of nature (listening to the sound of the bird/rasi) to determine the type of land suitable for farming (bahuma); offerings as a means to communicate with Jubata, ghosts, demons/devils; and offerings as symbols of gratitude, sacrifice, restoration of relationships, purity, and sincerity. (2) The tone includes the tone of gratitude, the tone of surrender, the tone of the sacred; pleading tone, friendly tone, and hopeful tone. (3) Feelings include feelings of joy, optimism, cooperation, togetherness, solidarity, and full of blessings. (4) Mantra's mandate includes that humans must be able to establish good communication with Jubata, the spirits of the ancestors, and the devil so that they can coexist and not be disturbed by the power of the devil; the implementation of the Baburukng ritual is a form of obedience to tradition and complete surrender to Jubata; cooperation, togetherness, and high solidarity need to be preserved. The forms of local wisdom in the Nyangahatn Baburukng text include (1) local knowledge; (2) local values; (3) local skills and technology; and (4) elements of local leadership.Nyangahatn Baburukng adalah mantra komunitas Dayak Kanayatn yang diucapkan pada ritual Baburukng sebagai tahap awal dari tradisi berladangan (bahuma). Kajian ini dilakukan untuk memberikan makna yang lebih mendalam terhadap struktur batin dan kearifan lokal Nyangahatn Baburukng dan sebagai alat pewarisan kepada generasi penerus. Objektif kajian dalam penelitian ini adalah penganalisisan terhadap struktur batin dan bentuk-bentuk kearifan lokal dalam Nyangahatn Baburukng. Kajian didasarkan pada teori-teori kearifan lokal, mantra, dan struktur mantra dengan menggunakan metode deskriptif kualitatif, pendekatan objektif dan sosiologi sastra. Hasil penelitian ini menunjukkan bahwa struktur batin teks Nyangahatn Baburukng meliputi (1) Tema meliputi keyakinan kepada Jubata sebagai penolong dan pemberi berkat; cermat membaca tanda-tanda alam (mendengarkan bunyi burung/rasi) untuk menentukan jenis lahan yang cocok untuk berladang (bahuma); persembahan sebagai sarana untuk berkomunikasi dengan Jubata, hantu, setan/iblis; dan bahan-bahan persembahan sebagai simbol dari rasa syukur, pengorbanan, pemulih hubungan, kesucian, dan keikhlasan. (2) Nada meliputi nada bersyukur, nada penyerahan diri, nada sakral; nada memohon, nada bersahabat, dan nada penuh harapan. (3) Rasa meliputi rasa gembira, optimis, kerjasama, kebersamaan, solider, dan penuh berkat. (4) Amanat mantra meliputi manusia harus mampu membangun komunikasi yang baik dengan Jubata, roh para leluhur, dan iblis agar dapat hidup berdampingan dan tidak terganggu oleh kuasa iblis; pelaksanaan ritual Baburukng merupakan wujud kepatuhan pada tradisi dan penyerahan diri sepenuhnya kepada Jubata; kerja sama, kebersamaan, dan solidaritas yang tinggi perlu terus dilestarikan. Bentuk-bentuk kearifan lokal dalam teks Nyangahatn Baburukng meliputi (1) pengetahuan lokal; (2) nilai-nilai lokal; (3) keterampilan dan teknologi lokal; dan (4) unsur kepemimpinan lokal.